2010
DOI: 10.1592/phco.30.8.787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proton Pump Inhibitors on the Effectiveness of Clopidogrel After Coronary Stent Placement: The Clopidogrel Medco Outcomes Study

Abstract: Concomitant use of a PPI and clopidogrel compared with clopidogrel alone was associated with a higher rate of major adverse cardiovascular events within 1 year after coronary stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
1
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 20 publications
(27 reference statements)
4
116
1
18
Order By: Relevance
“…Several observational studies have shown significant associations between PPI use and cardiovascular events. [27][28][29][30][31] However, other retrospective analyses (including observational and post hoc analyses of randomized trials) [32][33][34] and the only randomized, clinical trial evaluating the potential interaction between clopidogrel and a PPI (omeprazole) failed to show an increased risk of adverse cardiovascular events among PPI users, irrespective of the type of PPI. 35 With regard to pantoprazole, a population-based, nested, case-control study of patients receiving clopidogrel therapy after acute myocardial infarction showed that pantoprazole was not associated with an increase in cardiac events, whereas other PPIs were.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have shown significant associations between PPI use and cardiovascular events. [27][28][29][30][31] However, other retrospective analyses (including observational and post hoc analyses of randomized trials) [32][33][34] and the only randomized, clinical trial evaluating the potential interaction between clopidogrel and a PPI (omeprazole) failed to show an increased risk of adverse cardiovascular events among PPI users, irrespective of the type of PPI. 35 With regard to pantoprazole, a population-based, nested, case-control study of patients receiving clopidogrel therapy after acute myocardial infarction showed that pantoprazole was not associated with an increase in cardiac events, whereas other PPIs were.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı çalışmalarda perkütan koroner girişim sonrası majör AKS insidansında artma gösterilirken bazı çalışmalarda ise herhangi bir önemli klinik etkileşim izlenmemiştir (16)(17)(18) . Yukarıda belirtilen sonuçlardan sonra bazı yazarlar ranitidin veya diğer H2-reseptör antagonistlerinin kullanımını önermişlerdir.…”
Section: öZetunclassified
“…When patients on each proton pump inhibitor were analyzed separately, there were no differences in the percent of patients with a cardiac event: omeprazole 25%, esomeprazole 25%, lansoprazole 24%, and pantoprazole 29%. Given the marked differences in CYP2C19 inhibition between omeprazole and esomeprazole versus lansoprazole and pantoprazole, qualitative differences between the groups would have been expected [74]. Two other smaller analyses also supported the greater risk of cardiac events with patients receiving concurrent proton pump inhibitors but again, whether the additional risk is due to the underlying differences in the populations versus the use of the drug cannot be determined [75,76].…”
Section: Drug Interactions Impeding Cardiovascular Drug Functionmentioning
confidence: 99%